Rapid and Effective Virucidal Activity of Povidone-Iodine Products Against Middle East Respiratory Syndrome Coronavirus (MERS-CoV) and Modified Vaccinia Virus Ankara (MVA). Issue 4 (December 2015) - Eggers, Maren; Eickmann, Markus; Zorn, Juergen
Abstract Introduction Since the first case of Middle East Respiratory Syndrome coronavirus (MERS-CoV) infection was reported in 2012, the virus has infected more than 1300 individuals in 26 countries, and caused more than 480 deaths. Human-to-human transmission requires close contact, and has typically occurred in the healthcare setting. Improved global awareness, together with improved hygiene practices in healthcare facilities, has been highlighted as key strategies in controlling the spread of MERS-CoV. This study tested the in vitro efficacy of three formulations of povidone iodine (PVP-I: 4% PVP-I skin cleanser, 7.5% PVP-I surgical scrub, and 1% PVP-I gargle/mouthwash) against a reference virus (Modified vaccinia virus Ankara, MVA) and MERS-CoV. Methods According to EN14476, a standard suspension test was used to assess virucidal activity against MVA and large volume plating was used for MERS-CoV. All products were tested under clean (0.3 g/L bovine serum albumin, BSA) and dirty conditions (3.0 g/L BSA + 3.0 mL/L erythrocytes), with application times of 15, 30, and 60 s for MVA, and 15 s for MERS-CoV. The products were tested undiluted, 1:10 and 1:100 diluted against MVA, and undiluted against MERS-CoV. Results A reduction in virus titer of ≥4 log10 (corresponding to an inactivation of ≥99.99%) was regarded as evidence of virucidal activity. This was achieved versus MVA and MERS-CoV, under both clean and dirty conditions, within 15 s of application of each undiluted PVP-I product. Conclusion These data indicate that PVP-I-based hand wash products for potentially contaminated skin, and PVP-I gargle/mouthwash for reduction of viral load in the oral cavity and the oropharynx, may help to support hygiene measures to prevent transmission of MERS-CoV. Funding Mundipharma Research GmbH & Co.